Structure, retrogradation and digestibility of waxy corn starch modified by a GtfC enzyme from Geobacillus sp. 12AMOR1. (April 2022) - Li, Xiaolei; Wang, Yong; Mu, Siyu; Ji, Xiangqing; Zeng, Cheng; Yang, Dingkuan; Dai, Liyuan; Duan, Cuicui; Li, Dan
Abstract: To lower the retrogradation and digestibility of waxy corn starch for different food applications, a novel thermostable GtfC type 4, 6-α-glucanotransferase without N- and C- terminals (GsGtfC) from Geobacillus sp. 12AMOR1 was used. Waxy corn starch of 50 g/L was incubated with GsGtfC of 40–100 U/g substrate at 65 °C and pH 5.5 for 1 h. Its molecular weight, iodine affinity, XRD crystallinity, and FTIR ratio of heights of bands at 1047 and 1022 cm −1 decreased, but ratio of DP<6 to DP≥25 branches and degree of branching increased. GsGtfC cleaved α-1, 4-glycosidic bonds and induced α-1, 6-branching points to produce reuteran-likes polymers, which is different from Exiguobacterium sibiricum GtfC enzyme cleaving α-1, 4-glycosidic bonds and synthesizing consecutive α-1, 6-glycosidic bonds to produce isomalto/malto-oligosaccharides. GsGtfC modified waxy corn starch had significantly lower DSC retrogradation enthalpies during the storage at 4 °C for 3–14 days and significantly lower released glucose during the incubation with mammalian mucosal α-glucosidase at 37 °C for 10–360 min. GsGtfC at 100 U/g substrate increased slowly digestible portion from 11.07% to 24.11%. Graphical abstract: Image 1